Mexican Validation of the MOS Questionnaire on Perceived Social Support in the Context of the COVID-19 Pandemic - Del Carpio Ovando, Perla Shiomara (2022)
Introduction: The COVID-19 pandemic has had a very negative impact on people’s overall mental health and psychosocial well-being, but the study of available social support to cope with such an adverse situation has received hardly any attention. Objective: To exa-mine the psychometric properties of the MOS Perceived Social Support Questionnaire among the Mexican population in the context of the COVID-19 pandemic. Method: Non-experimental cross-sectional study. A sociodemographic questionnaire and the Medical Outcomes Study were applied in a non-probabilistic sample. A total of 898 people from different regions in Mexico, 258 males and 640 females, participated in the study in the context of the COVID-19 pandemic. Results: The analysis yielded a bi-factor model with two factors, Emotional/informational support and Tangible support, with satisfactory goodness of fit indices. Reliability was adequate with a high hierarchical omega coefficient, as well as in the factors. Likewise, the H coefficient was adequate in the general factor and its dimensions. Conclusions: Results showed that the scale is a valid and reliable measure of perceived social support among the Mexican population.